Preparation and pharmacological effects of minor ginsenoside nanoparticles: a review - Ke, Yue; Huang, Lei; Song, Yu; Liu, Zhenxin; Liang, Linshuang; Wang, Linmao; Wang, Taoyun (Frontiers in Pharmacology, 2022)
Ginseng (Panax ginseng) is a perennial herbaceous plant belonging to Panax genus of Araliaceae. Ginsenosides are a kind of important compounds in ginseng and minor ginsenosides are secondary metabolic derivatives of ginsenosides. Studies have shown that minor ginsenosides have many pharmacological effects, such as antioxidant, anti-tumor, anti-platelet aggregation, and neuroprotective effects. However, the therapeutic effects of minor ginsenosides are limited due to poor solubility in water, short half-life, and poor targeting accuracy. In recent years, to improve the application efficiency, the research on the nanocrystallization of minor ginsenosides have attracted extensive attention from researchers. This review focuses on the classification, preparation methods, pharmacological effects, and action mechanisms of minor ginsenoside nanoparticles, as well as existing problems and future direction of relevant research, which provides a reference for the in-depth research of minor ginsenoside nanoparticles.